Cycling during COVID-19 Pandemic: Sports or Lifestyle? - Budi, D. R.; Widyaningsih, R.; Nur, L.; Agustan, B.; Dwi, D. R. A. S.; Qohhar, W.; Asnaldi, A. (International Journal of Human Movement and Sports Sciences, 2021)
The increasing trend of cycling during the Covid-19 pandemic is a common social phenomenon that is common in various countries. This study aims to overview the cycling phenomenon during the Covid-19 Pandemic and the factors causing the cycling trend during a pandemic. In addition, the main highlight is to determine the emergence background of the cycling trend; whether it is an increase in people's awareness of sports or is it merely a lifestyle trend? The research method uses a systematic literature review by conducting literature reviews in reputable journals and scientific publications that discuss cycling in the pre-pandemic and pandemic times. Data analysis uses descriptive analysis and phenomenological approach as a theoretical framework. The results showed that four factors caused the cycling trend during the pandemic. Those factors are health, environment, media and lifestyle factors. Health reasons are due to the desire to maintain health and body immunity, and cycling is a sport recommended by health experts and according to the principle of physical distancing. Environmental factors are caused by being economical and environmentally friendly, supporting the "go green" program, and cyclist could get fresh and clean air. The media factor is driven by the significant influence of social media content and hashtags about cycling. While lifestyle factors arise due to following the latest trends, cycling can relieve stress and increase social status indicated by the price of bicycles and reasons for conformity in social groups. The increasing trend of cycling is mainly motivated by the desire to accompany the social demands of the current lifestyle, while the motivation related to health factors to increase body immunity in dealing with pandemic situations is secondary motivation. This conclusion is obtained based on the instability of the cycling trend and the downward trend in the cycling intensity graph.